Theoretical Analysis of Coupling Constant, Longitudinal Modes, and Threshold Gain for Coupled-Cavity Semiconductor Lasers - A. Hubeatir, Kadhim; A. Mahdi, Mohammed; Jabur Al-Azawi, Razi (Journal of Engineering and Sustainable Development, 2009)
A theoretical analysis of the coupled-cavity semiconductor laser requires simultaneous consideration of the gain and loss in the two cavities after taking into account their mutual optical feedback. Is wavelength-independent (and hence the same for all Fapry-perot (FP), in a coupled-cavity laser the effective facet loss becomes different.